Finance Disclosure and Its Role in Attracting Foreign Investment - Al-Badri, Saud Jabbar Mohammed (University of Thi-Qar Journal, 2025)
The developing countries face significant financial challenges that lead to a deficit in their local investments, which drives them to search for alternatives like foreign direct investment. This type of investment is an effective means to improve the national economic climate, as it directly supports the economic system by pumping capital and providing new job opportunities. In addition, FDI plays a pivotal role in transferring technology and knowledge, assisting in addressing balance of payments deficit and improving macroeconomic indicators, aided by incentives and removal of barriers to expedite the entry of foreign investments. Developing countries face numerous challenges related to the opacity in financial reports, as many studies have shown that foreign investors often grapple with inaccurate information and limited disclosure in annual reports, especially in the wake of recent economic and financial shocks. This lack of transparency negatively impacts trust in financial data, leading to erroneous investment decisions and threatening the stability of economic institutions. In light of this, enhancing financial disclosure becomes a critical need, as providing reliable and transparent financial reports is essential for supporting informed decision-making by investors and stakeholders. The importance of accounting disclosure emerges as it is the main means of presenting the financial results of institutions and conveying a true picture of their financial situation, which enhances public trust and stimulates more foreign direct investments, thereby supporting economic growth and financial stability in host countries.